PENGEMBANGAN MODEL INTERNALISASI NILAI KARAKTER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI VCT (VALUE CLARIFICATION TECHNIQUE) DI SMA NEGERI 6 PALEMBANG - Harto, Kasinyo (Intizar, 2015)
AbstractThis paper is a research result that reviews the way to internalize character values through VCT (Value Clarification Technique) in Islamic education by conducting a case study at SMAN 6 Palembang. The procedure of developing the character internalization model through VCT is also discussed. The implementation of VCT at SMAN 6 Palembang is conducted by the teachers through some stages: First, teacher conducts the learning process in accordance with the lesson plans to make the students internalize the values and perform appropriate attitude. Second, teacher does the assessment through written test and affective evaluation. Third, teacher gives remediation for those who do not meet the minimum standard score. Thus, the implementation of VCT in the subject of Islamic education at SMAN 6 Palembang has been conducted by the teachers through various materials starting from opening the class, discussing and assessing the students by written and unwritten evaluation.Â Keywords: Islamic education, VCT